Peran Digital Marketing dan Service Quality terhadap Customer Engagement melalui Customer Satisfaction: Studi pada Pelanggan Shopeefood Mahasiswa Bandung - Muhammad Rizal Ar Rasyid; Mahir Pradana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the role of digital marketing and service quality on customer engagement with the mediation of customer satisfaction in ShopeeFood customers among Bandung students. The implications of this study provide insight for food delivery service companies to focus on digital marketing strategies and improving service quality to increase customer satisfaction and engagement. ShopeeFood is a marketplace-based e-commerce company originating from Singapore under the auspices of the SEA Group. In 2015 Shopee was officially introduced in Indonesia. ShopeeFood is an e-commerce platform that is experiencing rapid growth in Southeast Asia, used to buy and sell products online. This research is classified as research with a quantitative approach. The data obtained is primary data obtained through data collection using a questionnaire to 150 respondents who use ShopeeFood services and live in Bandung City. The questionnaire was distributed to respondents via Google Form and conducted online using social media platforms to collect data. Data analysis and data processing were carried out using SmartPLS 3.2.9. The results of this study indicate that digital marketing has an effect on customer satisfaction, digital marketing has no effect on customer engagement, service quality has an effect on customer satisfaction, service quality has an effect on customer engagement, customer satisfaction has an effect on customer engagement, digital marketing through customer satisfaction has an effect on customer engagement, service quality through customer satisfaction has an effect on customer engagement.